From Food to Memory: Tourists’ Perceived Value of Gastronomy Tourism Contributing to Destination Development - Vithayaporn, Sanhakot; Songsakul, Jarujan; Cheewaprapanan, Areewan (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study explores the multifaceted role of gastronomy tourism in destination development, emphasizing the significance of tourists’ perceived value in shaping experiential and strategic outcomes. Using a systematic literature review guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, the research synthesizes high-quality scholarly sources to address three key questions: (1) To what extent does gastronomy tourism contribute to destination development? (2) How does gastronomy tourism influence the shaping and evolution of destination development strategies? (3) What is the impact of tourists’ perceived value of gastronomy tourism on destination development? The findings reveal that gastronomy tourism is not merely a supplementary attraction but a dynamic and transformative force that contributes to economic vitality, cultural preservation, and community engagement. Tourists perceived value—shaped by culinary authenticity, emotional resonance, and participatory experiences—plays a pivotal role in enhancing satisfaction and influencing destination image and loyalty. Moreover, gastronomy has become a strategic asset in place branding and sustainable tourism planning. This study contributes to a deeper theoretical and practical understanding of how food-related experiences evolve into memorable elements of travel, leaving lasting impressions that support long-term destination competitiveness. Implications for policy, tourism marketing, and local stakeholder engagement are discussed, along with recommendations for future research to explore emerging trends and interdisciplinary approaches in gastronomy tourism.